Pengaruh Emotional Freedom Technique (EFT) Terhadap Gambaran Diri Pasien Kanker Payudara di Yogyakarta - Eki Resti Anggreini; Ike Wuri Winahyu Sari (PSIK FKKMK UGM, 2021)
Background: Mastectomy and chemotherapy have side effects that can affect the body image of breast cancer patients. The Emotional Freedom Technique (EFT) is a complementary alternative medicine that has the power of tapping and suggestion that can correct physical and psychological problems in just minutes.Objective: The aim of this study was to determine the effect of EFT on the body image of breast cancer patients in one of hospital in Yogyakarta.Methods: This study used a pre-experimental design with one group pre-test and post-test designs. The sampling used purposive sampling technique with a sample size of 17 respondents. The body image was measured using a valid and reliable Body Image Scale (BIS). Data were analysed using the Wilcoxon test.Results: The body image of breast cancer patients before being given an EFT showed a median value of 8,00 (range of score from 0-30). Meanwhile, respondent’s body image after being given EFT showed a median value of 4,00 (range of score 0-30). Wilcoxon test results obtained a p-value of <0,001, which means that there was a significant effect of EFT on the body image of breast cancer patients.Conclusion: There is an effect of EFT on the body image of breast cancer patients. EFT therapy is a non-pharmacological alternative therapy that can be applied to improving negative body image in breast cancer patients. ABSTRAKLatar Belakang: Pengobatan kanker payudara seperti mastektomi ataupun kemoterapi memiliki efek samping yang dapat memengaruhi gambaran diri pasien kanker payudara. Emotional Freedom Technique (EFT) merupakan pengobatan komplementer alternatif yang mempunyai kekuatan tapping dan sugesti yang bisa memperbaiki masalah fisik dan psikologis hanya dalam waktu hitungan menit.Tujuan: Untuk mengetahui pengaruh Emotional Freedom Technique (EFT) terhadap gambaran diri pasien kanker payudara di Yogyakarta.Metode: Penelitian ini menggunakan desain pre experiment dengan rancangan one group pretest and posttest. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel sebanyak 17 responden. Gambaran diri diukur menggunakan Body Image Scale (BIS) yang telah valid dan reliabel. Analisis data menggunakan uji Wilcoxon.Hasil: Gambaran diri pasien kanker payudara sebelum diberikan EFT menunjukkan nilai median 8,00 (rentang skor 0-30). Sementara gambaran diri responden setelah diberikan EFT menunjukkan nilai median 4,00 (rentang skor 0-30). Hasil uji Wilcoxon diperoleh p-value <0,001.Kesimpulan: Terdapat pengaruh EFT terhadap gambaran diri pasien kanker payudara. Terapi EFT merupakan pengobatan alternatif non farmakologi yang dapat diterapkan dalam memperbaiki gambaran diri yang negatif pada pasien kanker payudara.